Family Policy and the Organisation of Childcare Hierarchies of Care Ideals - Kovács, Borbála (Springer International Publishing, 2018)
This book explains and theorises the ways in which family policy instruments come to shape the routine care arrangements of young children. Drawing on interviews with close to a hundred parents from very different walks of life in urban and rural Romania, the book provides a rich account of the care arrangement transitions these parents experience during their children's first five years of life. The influence of family policies emerges as complex and uneven, affecting childcare decisions both directly and indirectly by contributing to the reproduction and legitimation of age-related hierarchies of care ideals. These cultural artefacts, reflective of both longstanding institutional legacies and recent policy innovations between 2006 and 2015, are the prism through which mothers and fathers from diverse backgrounds view and make decisions about their children's care. This unique volume will be of interest and value to students and scholars of childcare, its organisation and family policy, specifically in post-socialist contexts.